Morbidity trend and space-time clusters of COVID-19 occurrence in children and adolescents - Camila Beatriz Alves da Rocha; Lúbia Maieles Gomes Machado; Pãmela Rodrigues de Souza Silva; Bruna Hinnah Borges Martins de Freitas; Iara Denise Endruweit Battisti; Emerson Soares dos Santos; Silvana Margarida Benevides Ferreira (Elsevier, 2024)
Objective: To analyze the morbidity trend and space-time distribution clusters of confirmed COVID-19 cases in children and adolescents. Method: An ecological study of COVID-19 cases confirmed in the Information System from 2020 to 2022 in the age group from 0 to 19 years old, residents in Mato Grosso municipalities, Brazilian Midwest region. A trend analysis of the monthly morbidity rate of cases/100,000 inhabitants was used, following Prais-Winsten's regression. A space-time distribution of the Bayesian incidence rate per 100,000 inhabitants was performed, in addition to a space-time scan to identify high-risk clusters. Results: Of all 79,592 COVID-19 cases studied, 51.6% were in females and 44.21% in people aged 15-19 years old. The mean monthly rate was 265.87 cases per 100,000 inhabitants, with a stationary trend in the period analyzed (Monthly Percentage Variation [MPV]) = 12.15; CI95%[MPV]: -0.73;26.70). The morbidity rate due to COVID-19 was higher in the female gender (283.14/100,000 inhabitants) and in the age group from 15 to 19 years old (485.90/100,000 inhabitants). An increasing trend was observed with a greater monthly time variation of 14.42% (CI95%[MPV]: 1.28;29.28)] among those aged from 10 to 14 years old. The primary cluster, which was also the one with the highest Relative Risk (RR = 5,16, p-value = 0.001), included 19 municipalities located in the North health macro-region. Conclusion: The findings indicated a monthly stationary trend in the study population, an increase in the age group from 10 to 14 years old, and areas at a higher risk for the disease in the North health macro-region of the state.